Development and validation of a Mental Health Self-Care Scale in Peruvian adults Mental Health Self-Care in Peruvian adults - Lam-Flores, Silvia L. (2026)
Introduction: Mental health care has been identified as an important component within the overall health response to the COVID-19 pandemic.  The study aimed to develop and validate the Mental Health Self-Care Scale (ESAMEN), gathering evidence about its factorial and convergent validity and its internal consistency.  Method: Peruvian adults of both sexes in 2021 participated in the study. An exploratory factor analysis was performed to identify the structure of the mental health self-care variable. Results: A structure with three dimensions was identified: mental (α = 0.95), social (α = 0.95), and spiritual (α = 0.96).  Corroborating the evidence of convergent validity, the dimensions of the ESAMEN showed expected correlations with measures of self-esteem, self-efficacy, eustress, and distress. Conclusion: The final version of the ESAMEN, consisting of 16 items, presents adequate psychometric evidence to assess mental health self-care, and can be used in studies in the Peruvian context.